2014
DOI: 10.1680/si.13.00018
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of electrospun polycaprolactone fibers and effect on cell proliferation

Abstract: Surface modification is an essential tool in tissue engineering using synthetic biomaterial scaffolds. The authors report in this study a simple approach to modify the surface hydrophobicity, roughness and chemistry of electrospun polycaprolactone (PCL) fibers using a combination of oxygen plasma treatment, sodium hydroxide treatment and arginine–glycine–aspartic acid (RGD) immobilization. The modified surfaces were characterized using scanning electron microscopy, atomic force microscopy, water contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In addition to the incorporation of nHA, the arrangements of nanofiber either in aligned or random orientation can also affect the nanofiber surface roughness value. PCL fibers with an aligned arrangement had a smooth surface (Ahmad et al 2014). In a random orientation, a higher surface roughness was observed (Dias and Bártolo 2013;Lim et al 2015).…”
Section: Wettability and Surface Roughness Of Nanofibersmentioning
confidence: 92%
“…In addition to the incorporation of nHA, the arrangements of nanofiber either in aligned or random orientation can also affect the nanofiber surface roughness value. PCL fibers with an aligned arrangement had a smooth surface (Ahmad et al 2014). In a random orientation, a higher surface roughness was observed (Dias and Bártolo 2013;Lim et al 2015).…”
Section: Wettability and Surface Roughness Of Nanofibersmentioning
confidence: 92%
“…31 PCL is an aliphatic semi-crystalline polymer successfully designed to meet the needs of a biomaterial for regenerative purposes in the field of tissue engineering due to its physicochemical properties. 32 It is highly hydrophobic, so it is commonly mixed with hydrophilic polymers such as Alginate, gelatine and proteoglycans to improve its biocompatibility and enhance cell growth and expansion. 32 A great variety of bioactive molecules, growth factors and cells may be incorporated into its core or surface to provide osteo-inductive and/or antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in this review demonstrated that PCL is highly compatible, yet its hydrophobicity clearly modulates cell dynamics, which improves when PCL is combined with hydrophilic polymers and coatings. 32,33 PLGA, a copolymer made of a combination of lactic and glycolic acid has proven to favor PCL scaffolds biocompatibility by enhancing fibroblast growth, in in vitro experimental models. 34 PLGA also allows to modulate the degradation rate of PCL, which is significantly low; It takes approximately two and a half years to be completely resorbed.…”
Section: Days Of Culturementioning
confidence: 99%
“…The hydrophilicity of the material is important to know because a good scaffold must be able to facilitate cells to attach and proliferate. It is known from previous research that very hydrophilic or highly hydrophobic materials do not support cell attachment and proliferation [28]. A scaffold surface with moderate hydrophilicity (40-70°) is known to be the most optimal for protein absorption and cell response [29].…”
Section: Contact Anglementioning
confidence: 99%